New species and records of Dissomphalus Ashmead (Hymenoptera, Bethylidae) from Cerrado, Caatinga and relicts of the Atlantic Forest from northeastern Brazil - Colombo, Wesley D.; Alencar, Isabel D.c.c.; Limeira-De-Oliveira, Francisco; Azevedo, Celso O. (Zootaxa, 2018)
The main goal of this paper is to study the Dissomphalus material deposited at the Coleção Zoológica do Maranhão (Maranhão, Brazil). The material was collected in six parks: Parque Nacional Chapada das Mesas, Parque Estadual do Mirador and Reserva Ecológica do Inhamum in the state of Maranhão; Parque Nacional Serra das Confusões and Parque Nacional de Sete Cidades in the state of Piauí, and Parque Nacional de Ubajara in the state of Ceará. Forty species are recognized from these six parks. Twenty-two of them are previously described species, namely: D. bifurcatus Azevedo, D. cervoides Azevedo, D. conicus Azevedo, D. curvilongus Azevedo, D. geniculatus Azevedo, D. gilvipes Evans, D. infissus Evans, D. krombeini Azevedo, D. laminaris Redighieri & Azevedo, D. latimerus Azevedo, D. linearis Azevedo, D. lobisserratus Azevedo, D. magnus Redighieri & Azevedo, D. megomphalus Evans, D. microstictus Evans, D. napo Evans, D. plaumanni Evans, D. scamatus Azevedo, D. subpilosus Azevedo, D. tubulatus Redighieri & Azevedo, D. ubracus Brito & Azevedo and D. verrucosus Redighieri & Azevedo. Eighteen species are newly described and illustrated: Dissomphalus acutipupu Colombo & Azevedo sp. nov., D. boibumba Colombo & Azevedo sp. nov., D. boitata Colombo & Azevedo sp. nov., D. boiuna Colombo & Azevedo sp. nov., D. boto Colombo & Azevedo sp. nov., D. caipora Colombo & Azevedo sp. nov., D. capelobo Colombo & Azevedo sp. nov., D. cuca Colombo & Azevedo sp. nov., D. curupira Colombo & Azevedo sp. nov., D. iara Colombo & Azevedo sp. nov., D. iracema Colombo & Azevedo sp. nov., D. irupe Colombo & Azevedo sp. nov., D. joaquinae Colombo & Azevedo sp. nov., D. jurupari Colombo & Azevedo sp. nov., D. mapinguari Colombo & Azevedo sp. nov., D. matintaperera Colombo & Azevedo sp. nov., D. saci Colombo & Azevedo sp. nov. and D. torem Colombo & Azevedo sp. nov.. A key for these species is provided. The genus is newly recorded from the state of Piauí, Brazil.